Aloe Vera alleviates glyphosate-based herbicide hepatotoxicity in rats via anti-inflammatory and antioxidant actions - Hamad, Nashwa; Sharkawy, Ahmed A.; Ibrahim, Nagwa; Osman, Amany Abdel Rahman; Aljohani, Abdullah S. M.; Kamaly, Heba F. (Frontiers in Veterinary Science, 2025)
IntroductionGlyphosate-Based Herbicide (GBHs) are widely used worldwide, this study investigated the ameliorative effect of Aloe Vera against GBHs hepatic toxicity in rats via anti-inflammatory and antioxidant Actions, with a focus on DNA damage and apoptosis.MethodsTwenty-four Sprague–Dawley rats were randomly classified into four groups: Group I, represented as a control. In group II, rats were administered 500 mg/kg of Roundup herbicide as one of GBHs. In Group III, rats were administered 200 mg/kg of Aloe Vera, and finally, in Group IV, rats were co-administered with 500 mg/kg of Roundup and 200 mg/kg of Aloe Vera, orally, three times a week for 6 weeks.Results and DiscussionRats exposed to GBH showed significant oxidative stress, evidenced by elevated malondialdehyde (MDA) and decrease the reduced glutathione (GSH) levels, alongside increased the inflammatory markers (TNF-α and IL-1β). Liver function enzymes (ALT, AST, LDH) were markedly elevated, and comet assay results revealed substantial DNA fragmentation in hepatocytes. Histopathological findings and immunohistochemical overexpression of caspase-3 confirmed the liver pathological lesions and apoptosis, respectively. Co-administration of Aloe Vera with GBH significantly alleviated the biochemical, histopathological, and apoptotic alterations, but it did not fully reverse the DNA damage. These findings suggest that Aloe Vera may offer partial hepatoprotection against GBH toxicity through its antioxidant and anti-inflammatory properties.